Nizhne-Kurmoiarskaya loan-saving partnership in the credit and financial system of the Province of the Don Cossack Host - Olifirov K. A. (Interactive science, 2016)
the article analyzes the work of Nizhne-Kurmoiarskaya loan-saving partnership in the early 20th century. This credit institution activity is examined by means of considering the documents of Inspection of small loan of Rostov office of State Bank in 1912–1917. In order to understand the features of this partnership, the author takes into account some historical facts about small credit institutions. In conclusion the researcher outlines the significance and the basic operations of Nizhne-Kurmoiarskaya loan-saving partnership in the Province of the Don Cossacks Host.
Keywords: государственный банк; Инспекция по делам мелкого кредита Ростовской Конторы; учреждения мелкого кредита; ссудные операции; вкладные операции; State bank; Inspection of small loan of Rostov office; loan-saving partnerships; loan operations; depositary operations; ссудо-сберегательные товарищества; small loan institutions